2021
DOI: 10.21776/ub.apmba.2021.009.03.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Shopping and E-Wallet on Consumer Impulse Buying

Abstract: This research examines the influence of On-line Shopping and E-wallet on Impulse Buying. The existence of an online shopping phenomenon using digital wallet payments (e-wallets) is prevalent among the public recently. This study adopted a survey method with 200 respondents selected purposively from two large cities in East Java, Indonesia namely malls located in Malang and Surabaya. Using variables that consist of shopping variables consisted of: variety of choices, price level, sensory attribute, utilitarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 2 publications
(2 reference statements)
3
21
0
3
Order By: Relevance
“…In addition to this theory, this study aims to evaluate the moderating role of low distribution charges and low transit time in the relationship between the adoption of e-wallets and impulsive buying as this gap was identified by Qingyang et al (2018) and Efendi et al (2019) in the context of online businesses. Indeed, as customers are utilizing digital wallets for purchasing (Mainwaring et al, 2005;Ridaryanto et al, 2019;Rahayu & Prasetyatama, 2021;Sari et al, 2021;Yong Lee et al, 2021;Hidajat & Lutfiyah, 2022), this study aims to contribute to the overall knowledge about impulse buying, and the practices followed by online businesses to influence customers to make impulsive purchases, while also following sustainable environmental business practices.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this theory, this study aims to evaluate the moderating role of low distribution charges and low transit time in the relationship between the adoption of e-wallets and impulsive buying as this gap was identified by Qingyang et al (2018) and Efendi et al (2019) in the context of online businesses. Indeed, as customers are utilizing digital wallets for purchasing (Mainwaring et al, 2005;Ridaryanto et al, 2019;Rahayu & Prasetyatama, 2021;Sari et al, 2021;Yong Lee et al, 2021;Hidajat & Lutfiyah, 2022), this study aims to contribute to the overall knowledge about impulse buying, and the practices followed by online businesses to influence customers to make impulsive purchases, while also following sustainable environmental business practices.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Indeed, the role of digital money is critical in online purchasing (Lee et al, 2022) but this study did not discuss the factors that are motivating the public to adopt e-wallets. On the other hand, the outbreak of the pandemic shifted people toward e-wallet purchasing, although the variables influencing people to adopt e-wallets were not discussed by Sari et al (2021). Similarly, the role of low distribution charges and low transit time was not discussed in earlier studies (Rahayu & Prasetyatama, 2021;Shamim & Islam, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…In addition to it, business administration is responsible to ensure that the customers get the appropriate distribution charges because they always compare the distribution charges with the other brands as well (Parameswari & Ginny, 2022) . However, if the customers are provided with effective distribution charges that are according to their standard then they would develop more effective satisfaction with the brand at they would become the loyal customer of the brand because distribution charges matter a lot in the mature market (Habib & Qayyum, 2018;Sari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The management of any business has the responsibility to protect customer loyalty and customer satisfaction (Murad et al, 2022). It is due to the reason that the management is playing a key role in the success of the business with the help of customer management and protecting the rights of the stakeholders (Sari, Utama, & Zairina, 2021;Yulianto, Sisko, & Hendriana, 2021). In digital world, online business trend has emerged and people are utilizing different applications to purchase online from these businesses (Andrei, Popescu, Nica, & Chivu, 2020).…”
Section: Moderating Role Of Effective Managementmentioning
confidence: 99%
“…Internet also enables customers to undertake product comparisons and have simple access to product prices in order to make educated purchase decisions (Alrabei, Al-Othman, Al-Dalabih, Taber, & Ali, 2022;Bonfrer, Chintagunta, & Dhar, 2022;Jawabreh, Jahmani, Shukri, & Ali, 2022). (Sari, Utama, & Zairina, 2021) argue that internet shopping offers customers comfort and ease in relation to their buying desires. (Aryani et al, 2021) found that online shopping gives consumers quick access to their favorite brands and saves them time compared to purchasing in a physical store.…”
Section: Introductionmentioning
confidence: 99%